The Influence of Visionary Leadership, Motivation, and Organizational Culture on Employee Performance at the Regional Financial Agency of Pagar Alam City - Dhinda Putri Savina; Azwardi; Yomeini Margareth (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2026)
This study aims to determine the influence of visionary leadership, motivation, and organizational culture on employee performance at the Regional Finance Agency of Pagar Alam City. The research sample amounted to 70 employees of the Regional Finance Agency of Pagar Alam City. The data collection method was carried out through the distribution of questionnaires to respondents. The type of research used is quantitative research with multiple linear regression analysis to test the influence of independent variables on dependent variables. The results of the study show that visionary leadership, work motivation, and organizational culture have a positive and significant effect on employee performance. These findings show that the improvement in the performance of employees of the Pagar Alam City Regional Finance Agency is influenced by the clarity of the vision communicated by the leader, the work motivation that encourages employees to carry out their duties, and the existing organizational culture. This study recommends the importance of strengthening the role of visionary leadership, efforts to increase motivation, and organizational culture in order to support the effectiveness of organizational performance.